2023
DOI: 10.3390/f14102105
|View full text |Cite
|
Sign up to set email alerts
|

Flame-Retardant and Smoke-Suppression Properties of Bamboo Scrimber Coated with Hexagonal Boron Nitride

Gaihuan Li,
Ying Yu,
Shaofei Yuan
et al.

Abstract: In order to improve the flame-retardant properties of bamboo scrimber, chitosan (CS) and polyvinyl alcohol (PVA) were used as the film-forming substances, and hexagonal boron nitride (h-BN) was used as the flame-retardant substance to prepare h-BN flame-retardant coatings, which were coated on the surface of the bamboo scrimber. The effects of the h-BN flame-retardant coatings with different quality concentrations on the flame-retardant properties of the bamboo scrimber, as well as on the morphology of the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…BN has also found applications in flame-retardant composites [ 15 , 16 , 17 ]. In recent research from Yao et al [ 18 ], polyphosphazene-modified MH crosslinked by boric acid was reported to grow BN in situ, which hindered the transfer of volatile products and formed a compact char layer in the condensed phase of EVA.…”
Section: Introductionmentioning
confidence: 99%
“…BN has also found applications in flame-retardant composites [ 15 , 16 , 17 ]. In recent research from Yao et al [ 18 ], polyphosphazene-modified MH crosslinked by boric acid was reported to grow BN in situ, which hindered the transfer of volatile products and formed a compact char layer in the condensed phase of EVA.…”
Section: Introductionmentioning
confidence: 99%